Fiction as the Art of Words (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Just as artists paint a canvas with watercolors, oils or gouache, so writers, using fiction, words and language structures, create a work. Fiction acts on a par with other types of creativity - music, sculpture, painting. The subject of literature, like any other form of art, is objective reality, not limited by any boundaries.